2017
DOI: 10.17533/udea.iee.v35n3a07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the concept of powerlessness in individuals with stroke

Abstract: Objective: To identify and analyze the concept of the powerlessness in individuals with stroke, according to the NANDA-I Taxonomy. Methods. Concept analysis from online access of four databases using the descriptors: impotence; helplessness, learned; Stroke, depression in languages: Portuguese, English and Spanish. Results. The critical attributes of the feeling of powerlessness are: fragility, helplessness, lack of control, and power to achieve the proposed results for recovery and adaptation. Eleven new ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
6
0
4
Order By: Relevance
“…(6) A percepção de mudança na rotina e a incapacidade de executar atividades antes corriqueiras, pode acarretar um sentimento de impotência e provocar estresse. (25) O estresse quando perdura por período prolongado repercute sobre os aspectos físicos, sociais e emocionais, o que pode contribuir para o desenvolvimento de novas doenças. (26) Os níveis elevados de estresse aumentam o risco de novos episódios de AVE, além de predispor fatores de risco como hipertensão, diabetes mellitus e obesidade.…”
Section: Resultsunclassified
“…(6) A percepção de mudança na rotina e a incapacidade de executar atividades antes corriqueiras, pode acarretar um sentimento de impotência e provocar estresse. (25) O estresse quando perdura por período prolongado repercute sobre os aspectos físicos, sociais e emocionais, o que pode contribuir para o desenvolvimento de novas doenças. (26) Os níveis elevados de estresse aumentam o risco de novos episódios de AVE, além de predispor fatores de risco como hipertensão, diabetes mellitus e obesidade.…”
Section: Resultsunclassified
“…Resilience is the ability of the patient to deal with the adverse consequences of a stroke and maintain high life satisfaction despite challenges, including self-motivation, initiative, and compliance during rehabilitation (18,19). Fragility is the likelihood of a patient to retreat from life, socially isolate, suffer from poor life satisfaction, low self-esteem, and depression (20). Moreover, studies have identified several other important social factors impacting reintegration, such as environmental, socioeconomic, as well as family and social support (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…A comparação entre a situação atual com a antecedente ao AVE é bastante comum entre os sobreviventes. A percepção de mudança na rotina e a incapacidade de executar atividades antes corriqueiras podem acarretar um sentimento de impotência e provocar estresse (21) .…”
Section: Introdução Métodounclassified
“…A dependência da ajuda de terceiros para a realização das atividades de vida diária pode provocar um sentimento de inutilidade e frustração (8,16) . A percepção de mudanças na rotina e a incapacidade de executar atividades antes corriqueiras eleva os níveis de estresse, além de, frequentemente, compromer a autonomia e a qualidade de vida das pessoas acometidas por AVE (21) .…”
Section: Introdução Métodounclassified